(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In view of the many problems in the coating of the trademark, such as the poor stability of the filler, the poor adhesive resistance and ink absorption of the fabric, the high pH value and insufficient printing stability, etc. this paper focuses on the study of two kinds of common inorganic fillers, wollastonite and kaolin, on the structure of the polyamide 6 coating film and the properties of the wet coating trademark fabric. The mixture of these two kinds of filler is applied to the coating slurry, and the ratio and dosage are optimized. On this basis, combined with production practice, the wet coating process conditions were optimized. The results showed that the mass ratio of wollastonite and kaolin is 1:1 (the mass of the filler is 22% of anhydrous methanol), the compatibility of coating slurry is higher than that of the coating slurry prepared from single wollastonite, it is not easy to settle, but also the dispersion of coating slurry is better than that of only kaolin, and the microporous structure on the surface of coating film is more uniform. Moreover, the coated fabrics presented higher ink absorption performance. When the coating temperature is 35 25e6C, the viscosity of the coating is 2223c3 Pa00b7s, the baking temperature is 160 25e6C, and the baking time is 80 s. The color fastness to the soaping color of the coated fabric reaches to grade 4-5, the printing effect reaches to 3-4, the whiteness and the fabric style are better.